A clinical study of hypertensive emergencies - Konuganti, Sridhar Reddy; Swamy, Narsimha (International Journal of Research in Medical Sciences, 2020)
Background: Hypertensive crisis is characterized by high blood pressure that is highly likely to cause pressure against the arterial walls causing chronic cardiovascular diseases. It has caused higher mortality and morbidity rates in both adults and children in equal measures. Hypertensive emergency is scientifically believed to cause several vital organ failures. The current study aims to critically evaluate hypertensive emergencies and the spectrum of end-organ damage due to risk factors of hypertensive emergencies. Methods: This prospective study was conducted on 150 patients with a severe arterial blood pressure of >180/120 mmHg) admitted at Area hospital, Zaheerabad. The doctors performed a detailed medical and clinical examination on the patients to assess organ damage. 120 patients met the hypertensive emergency (HTN-E), while 30 patients met the hypertensive urgency (HTN-U). Results: Patients who reported signs of HTN-E were older adults who are more sedentary, highly intensive smokers, and non-adherent to all forms of hypertensive medications that those with HTN-U. Most of the HTC-U patients had a known history of hypertension than HTC-E. There is about 2% prevalence of hypertensive crisis while admitted at the ICU. Conclusions: Early assessment of the level of organ damage is key in regulating severe complications of hypertension.